2021
DOI: 10.3389/fcomm.2021.779814
|View full text |Cite
|
Sign up to set email alerts
|

Co-Speech Movement in Conversational Turn-Taking

Abstract: This study investigates co-speech movements as a function of the conversational turn exchange type, the type of speech material at a turn exchange, and the interlocutor’s role as speaker or listener. A novel interactive protocol that mixes conversation and (non-read) nursery rhymes works to elicit many speech turns and co-speech movements within dyadic speech interaction. To evaluate a large amount of data, we use the density of co-speech movement as a quantitative measure. Results indicate that both turn exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Flecha-García [55,56] found that brows tend to be raised in 'instruct moves' in dialogue games used for elicitation (the 'Map task' [57,58], e.g., "So then you go along just a few dashes" [55] (p. 68)). The role of eyebrow movement in turn-taking has been noticed in several studies [55,[59][60][61], e.g., insofar as, "more frequent and longer eyebrow-raising occurred in the initial utterance of high-level discourse segments than anywhere else in the dialogue" [55] (p. ii).…”
Section: Facial Gestures and Audiovisual Prosodymentioning
confidence: 93%
“…Flecha-García [55,56] found that brows tend to be raised in 'instruct moves' in dialogue games used for elicitation (the 'Map task' [57,58], e.g., "So then you go along just a few dashes" [55] (p. 68)). The role of eyebrow movement in turn-taking has been noticed in several studies [55,[59][60][61], e.g., insofar as, "more frequent and longer eyebrow-raising occurred in the initial utterance of high-level discourse segments than anywhere else in the dialogue" [55] (p. ii).…”
Section: Facial Gestures and Audiovisual Prosodymentioning
confidence: 93%
“…We make a distinction between speech in spontaneous communication scenarios and speech types that incorporate musical aspects, which may include prayers, mantras, chants, poems, nursery rhymes, freestyle rap and many other types of belief-based and/or artistic expressions (see Leong & Goswami 2015, Fuchs & Reichel 2016, Davis 2017, Cummins 2018, Danner et al 2021. All the latter tend to incorporate quasi-isochrony which should be related to the musical aspect of these complex fusions between music and speech.…”
Section: Isochrony Between Music and Speechmentioning
confidence: 99%
“…While gaze aversion and light indication helped decrease the interruptions, but they still occurred in most of the conversations. Turn-taking behavior can be further improved by using dialogue context (e.g., [75]), speech prosody (e.g., [76]), estimating the user's gaze, gestures, and facial expressions, such as eyebrow movement and mouth opening [77], or a combination of these features, e.g., [78][79][80] (for an in-depth review of turn-taking in HRI and conversational systems, see [81]) to prevent interrupting the user, both for improving user experience and speech recognition.…”
Section: Turn-takingmentioning
confidence: 99%